2021
DOI: 10.2147/pgpm.s319524
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role and Potential Mechanisms of the Ferroptosis-Related Metabolic Gene Signature in Hepatocellular Carcinoma

Abstract: Purpose Ferroptosis, as a novel regulated cell death form, has a close interaction with metabolism, which is largely unknown in cancer. In the present study, we conducted a comprehensive analysis of ferroptosis-related metabolic genes to delineate the metabolic signatures induced by ferroptosis and evaluate its prognostic significance in hepatocellular carcinoma (HCC). Methods The ferroptosis-related metabolic genes (Fer-MRGs) were identified by correlation analyses wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…When the body is in a state of OS, it may participate in the AA metabolic process because ROS can also oxidize blood and structural proteins and inhibit the proteolytic system (54). Dai et al (55) showed that cysteine limitation reduces the biosynthesis of glutathione (GSH) and causes the depletion of GSH, which directly inhibits the activity and stability of GPX4. In addition, cystathionine, cysteine and glycine are important precursors in the synthesis of GSH-Px, which has a rate-limiting role in the synthesis process (56).…”
Section: Discussionmentioning
confidence: 99%
“…When the body is in a state of OS, it may participate in the AA metabolic process because ROS can also oxidize blood and structural proteins and inhibit the proteolytic system (54). Dai et al (55) showed that cysteine limitation reduces the biosynthesis of glutathione (GSH) and causes the depletion of GSH, which directly inhibits the activity and stability of GPX4. In addition, cystathionine, cysteine and glycine are important precursors in the synthesis of GSH-Px, which has a rate-limiting role in the synthesis process (56).…”
Section: Discussionmentioning
confidence: 99%
“… 21 More than 50% of patients with liver cancer have slight iron overload and more than 80% of ferroptosis-related genes are different between HCC and normal tissues; high expression of GPX4, G6PD, and NQO-1 have been reported to be closely related to poor prognosis. 22 , 23 In this study, we identified the DEGs between HCC samples and normal liver samples, from TCGA database and GSE36376 database, and found 53 of them to be related to ferroptosis, further indicating the important role of ferroptosis in HCC. Ferroptosis is closely regulated by intracellular signaling pathways, including amino acid metabolism, lipid metabolism, and iron ion metabolism.…”
Section: Discussionmentioning
confidence: 81%
“…Numerous prognostic models for hepatocellular carcinoma have been reported previously. For example, ferroptosis-related and lipid metabolism-related prognostic model were established for prognostic analysis ( Hu et al, 2020 ; Dai et al, 2021 ). However, the prognostic model constructed by nucleotide metabolism-related genes has yet to be studied in depth.…”
Section: Discussionmentioning
confidence: 99%